POWER RELATIONS, SYMBOLIC RULES AND THE POSITION OF BELIS IN THE HABITUS OF THE NTT SOCIETY’S CUSTOMARY MARRIAGE - S. Rodliyah; A. Purwasito; B. Sudardi; Wakit Abdullah (Proceeding of International Conference on Art, Language, and Culture, 2019)
This study employs sociological-ethnographic basic method and the cultural studies paradigm as the approach in understanding the habitus within the customary marriage of the East Nusa Tenggara (NTT) society who require belis as a bride-price. The conceptual basis underlying the application of habitus theory and symbolic power in the NTT society refers to the Bourdieu’s framework. This study is a result of participatory observation on the habitus of a marital system using belis observed by the NTT society as a cognitive structure which connects individuals to the social activities of the customary marriage and makes it unquestionable habits. Knowledge of the social world under the pretext of prosperity for the recipients (family) of a bride-price can be a political instrument for the sustainability of power relations. The ritual-mythical system in the society has never been fully present as a neutral habit. The habitus reflected in the marital relationship among the NTT society enables the men to obtain and exercise their power relations. The sustainability of power relations can be seen from the representation of the social status of a girl and the properties attached to her. This is what gave birth to a symbolic rule, in which the social rules about bride-price or belis eventually will serve the interests of those who occupy a dominant position in the social structure, namely the rich men.